Improvement on a 2 × 2 Elements High-Gain Circularly Polarized Antenna Array. (22nd June 2015) - Liu, C.; Yan, A.; Yu, C.; Xu, T.
Abstract : A novel antipodal Vivaldi antenna with tapering serrated structure at the edges is proposed. Compared with traditional Vivaldi antennas without serrated structure, the gain of the designed antenna is significantly improved in the desired frequency band (4.5–7.5 GHz). In addition, a 2 × 2 Vivaldi antenna array with an orthorhombic structure is designed and fabricated to achieve a circular polarization (CP) characteristic. With this configuration, the 3 dB axial ratio bandwidth of the array reaches about 42% with respect to the center frequency of 6 GHz and a high gain is achieved as well. The novel Vivaldi antenna and CP antenna array both have ultrawide band (UWB) and high-gain characteristics, which may be applied to the field of commercial communication, remote sensing, and so forth.